Risk and prediction of dementia in patients with atrial fibrillation — A nationwide population-based cohort study. (15th November 2015) - Liao, Jo-Nan; Chao, Tze-Fan; Liu, Chia-Jen; Wang, Kang-Ling; Chen, Su-Jung; Tuan, Ta-Chuan; Lin, Yenn-Jiang; Chang, Shih-Lin; Lo, Li-Wei; Hu, Yu-Feng; Chung, Fa-Po; Tsao, Hsuan-Ming; et al.
Abstract: Background: Atrial fibrillation (AF) is associated with an increased risk of cognitive impairment and functional decline, and may contribute to development of dementia. Objectives: Data from a nationwide large-scale population-based cohort study are lacking. Besides, how best to predict the occurrence of incident dementia among AF subjects remains uncertain. Methods: A total of 332, 665 AF subjects without dementia were identified as the study group from the "National Health Insurance Research Database" in Taiwan. For each study patient, one age- and sex-matched subject without AF and dementia was selected as the control group. The study end point was occurrence of dementia, and the usefulness of CHADS2 and CHA2 DS2 -VASc scores in predicting dementia was analyzed. Results: During the follow-up, 29, 012 AF patients experienced dementia with an annual incidence of 2.12%, higher than non-AF subjects (1.50%). Patients with AF possessed a higher risk of dementia with a hazard ratio (HR) of 1.420 after adjustments for age, gender, baseline differences and medication use. Among AF patients, the CHADS2 and CHA2 DS2 -VASc scores were significant predictors of dementia with an adjusted HR of 1.520 and 1.497 per 1 increment of the CHADS2 and CHA2 DS2 -VASc scores, respectively. The c-index for CHA2 DS2 -VASc in predicting dementia (0.611, 95% confidence interval [CI] = 0.608–0.614) was significantly higher than the CHADS2 score (0.589, 95% CI = 0.586–0.592) (DeLong test p < 0.001). Conclusions: In this nationwide cohort study, AF was independently associated with a higher risk of dementia. The CHA2 DS2 -VASc score can be used to estimate the risk of dementia in AF patients.